ANALISIS PEMBIAYAAN KEPEMILIKAN RUMAH MELALUI DEVELOPER DENGAN AKAD ISTISHNA’ BERDASARKAN FATWA DSN MUI NO:06/DSN-MUI/IV/2000 TENTANG JUAL BELI ISTISHNA’ (Studi Kasus Developer Griya Wahid Asri Batang) - Miftahul Falah, Ahmad; Moegiri, M; Imtikhanah, Sobrotul (Neraca, 2023)
This study aims to determine the suitability of the application of the istishna’ buying and selling system on Public Housing Credit through developers in Griya Wahid Asri Batang with Fatwa DSN MUI NO: 06 / DSN-MUI / IV / 2000 concerning buying and selling istishna'. This research uses a qualitative approach. The data collection technique uses observation and interviews. The data analysis used in this study used qualitative descriptive methods. The research findings focus on the financing of home ownership supported by developers using an istishna' contract, in accordance with the rules provided in the DSN MUI Fatwa NO: 06/DSN-MUI/IV/2000. The primary objective of this study is to analyze the implementation of the contract in Developer Griya Wahid Asri Batang, with a particular emphasis on the examination of different provisions outlined in the aforementioned fatwa. These regulations address several issues pertaining to payment, commodities, and default. The application of the istishna' procurement and trade mechanism is consistent with the DSN MUI Fatwa NO: 06/DSN-MUI/IV/2000, which applies to the practice of istishna' buying and selling.   REFERENSI A’yun, Q. Q. (2021). Implementasi Fatwa Nomor 06/DSN-MUI/IV/2000 Tentang Jual Beli Istis {na>’Terhadap Pembiayaan Kepemilikan Rumah Syariah Di PT. Sabab Podho Moro Desa Sumberejo Kecamatan Geger Kabupaten Madiun. IAIN Ponorogo. Amri, M. A. (2019). Faktor-Faktor yang Mempengaruhi Keputusan Nasabah Bank OCBC NISP Medan Dalam Pemilihan KPR Konvensional dan Syariah. Universitas Islam Negeri Sumatera Utara. Antoni, A. (2019). ANALISIS PEMBIAYAAN PERUMAHAN SYARIAH NON BANK DI KOTA PALEMBANG. UIN Raden Fatah Palembang. Ariesto, H. S., & Arief, A. (2010). Terampil Mengolah data kualitatif dengan NVIVO. Jakarta: Prenada Media Group. Asiyah, B. (2015). Nur. Manajemen Pembiayaan Bank Syariah. Depok Sleman Yogyakarta: Penerbit Kalimedia. Az-Zuhaili, W. (2007). Fiqh al-islam wa adillatuhu, jilid V, Cet. X, Damaskus, Dar al-fikr. Bimantara, D., & Asari, A. (2022). Akad Analisis Akad Istishna Perspektif Fikih Muamalah dan Hukum Perdata. Mabsya: Jurnal Manajemen Bisnis Syariah, 4(2), 143–155. Chrisna, H., Karin, A., & Hasibuan, H. A. (2020). Analisis Sistem Dan Prosedur Kredit Kepemilikan Rumah (KPR) Dengan Akad Pembiayaan Murabahah Pada PT. BANK BRI Syariah Cabang Medan. Jurnal Akuntansi Bisnis dan Publik, 11(1), 156–166. Dewi, A. N. R., & Suryaningsih, S. A. (2020). PEMBIAYAAN KREDIT PEMILIKAN RUMAH SYARIAH NON-BANK DI TAHFIDZ RESIDENCE. Jurnal Ekonomika dan Bisnis Islam, 3(3), 221–233. Dr, P. (2008). Sugiyono, Metode Penelitian Kuantitatif Kualitatif dan R&D. CV. Alfabeta, Bandung, 25. Firmansyah, E. A., & Indika, D. R. (2017). Kredit pemilikan rumah syariah tanpa bank: studi di Jawa Barat. Jurnal Manajemen Teori dan Terapan, 10(3), 223–230. Haisyi, N. (2019). Analisis Terhadap Dalil Hukum dalam Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia Nomor 6 Tahun 2000 Tentang Istishna. At-Taradhi: Jurnal Studi Ekonomi, XI, 1, 25–36. Hardani, S. (2019). Pengembangan Sistem Informasi KPR Syariah dengan Metode Scrum. JITK (Jurnal Ilmu Pengetahuan Dan Teknologi Komputer), 4(2), 223–230. Heykal, M. (2014). Analisis Tingkat Pemahaman KPR Syariah pada Bank Syariah di Indonesia: Studi Pendahuluan. Binus Business Review, 5(2), 519–526. Hidayah, M. R., Nawawi, K., & Arif, S. (2018). Analisis Implementasi Akad Istishna Pembiayaan Rumah (Studi Kasus Developer Property Syariah Bogor). Jurnal Ekonomi Islam, 9(1), 1–12. Iswandi, I. (2022). IMPLEMENTASI AKAD ISTISHNA’PADA JUAL BELI RUMAH PERSPEKTIF FATWA MUI NO. 06/DSN-MUI/IV/2000: Studi Kasus di PT. Azzura Griya Utama Bekasi. Jurnal Penelitian Multidisiplin Ilmu, 1(4), 723–732. Moleong, L. J. (2014). Metode penelitian kualitatif edisi revisi. Bandung: PT Remaja Rosdakarya. Musbarina, M. (2021). Minat Nasabah Terhadap Kredit Pemilik Rumah di Bank Tabungan Negara Kantor Cabang Pembantu Syariah Parepare. IAIN Parepare. Paramansyah, A., Abdillah, I., & Damayanthi, D. (2021). Implementasi akad ba’i istishna dan ba’i taqsith pada pembiayaan kepemilikan rumah (non bank) di perumahan islami Indonesia. Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 3(1), 72–87. Rhosyidy, M. D. (2019). “Implementasi Akad Istishna’Dalam Kredit Pemilikan Rumah (Kpr) Syariah (Studi Kasus Pada Amany Residence Jember). Al-tsaman: Jurnal Ekonomi dan Keuangan Islam, 1(1), 40–60. Rifai, M. (2021). Konsep perbankan syariah. Rivai, V., & Arifin, A. (2010). Islamic banking: sebuah teori, konsep, dan aplikasi. PT Bumi Aksar. Sari, E. D. (2017). Tinjauan Ekonomi Islam Terhadap Kredit Pemilikan Rumah Syariah di PT. Hiba Mitra Devinda Kota Bengkulu. IAIN Bengkulu. Satria, M. R., & Setiani, T. (2018). Analisis Perbandingan Pemberian Kredit Pemilikan Rumah (KPR) Pada Bank Konvensional Dengan Pembiayaan Murabahah (KPR) Pada Bank Syariah (Studi Kasus Pada Bank BJB Dengan Bank BJB Syariah). Amwaluna: jurnal Ekonomi dan Keuangan syariah, 2(1), 105–118. Setiawan, A. (2016). Pemilihan Pembiayaan KPR (Kredit Pemilikan Rumah) dengan Akad Murabahah (Studi Kasus di Bank Muamalat Tbk Cabang Pembantu Samarinda Seberang). Al-Tijary, 17–24. Sundari, S., & Zuana, M. M. M. (2018). Analisis Implementsi Akad Istishna’Pembiayaan Rumah. Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 1(1), 49–59. Syah, J. R., & Harun, M. H. (2019). Jual Beli Istishna’Dalam Bisnis Kredit Pemilikan Rumah Syariah Griya Safa Perspektif Fatwa Dewan Syariah Nasional. Universitas Muhammadiyah Surakarta. Ubaidillah, M., Masnidar, M., & Muhammad, F. (2022). JUAL BELI ISTISHNA PERSPEKTIF FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA (STUDI PT. HUQY PROPERTI SYARIAH). UIN Sulthan Thaha Saifuddin Jambi. Wardhana, A., Kharisma, B., & Noven, S. A. (2020). Dinamika Penduduk Dan Pertumbuhan Ekonomi Di Indonesia. Buletin Studi Ekonomi. Vol, 25(1). Wiroso, W. (2011). Produk Perbankan Syariah. LPFE Usakti. Risgiyanti, R., & Hidayah, R. (2020). The role of workplace spirituality in reducing the negative impact of organizational cynicism on job performance. Jurnal Aplikasi Manajemen, 18(4), 692-703.  Riswan, R., & Suyono, E. (2016). Corporate diversification: Destroying or increasing firm value? Empirical evidence from Indonesia. Corporate Ownership & Control. 14 (4). Usamah, U. (2022). THE MODERATION ROLE OF GENDER ON THE FINANCIAL PERFORMANCE OF BAITUT TAMWIL MUHAMMADIYAH IN INDONESIA. Jurnal Ekonomi & Bisnis Islam, 8(1). Rosanti, C. (2020). Faktor-Faktor yang Mempengaruhi Inovasi Produk Koperasi Jasa Keuangan Syariah Pada KJKS BTM Se Jawa Tengah. Jurnal Ilmiah Ekonomi Islam, 6(1), 8-13. Susanti, L., & Triatmaja, M. F. (2023). Pengaruh Religiusitas Dan Green Consciousness Terhadap Keputusan Pembelian Sabun Cuci Green Wash. Media Ekonomi, 23(1), 1-12.